An overview on phytoconstituents and multiple biological activities of Euphorbia hirta - Chandel, Shobhini; Das, Saumya; Mazumder, Avijit; Neha; Chauhan, Vijayant Singh (Plant Science Today, 2023)
The major genus in the Euphorbiaceae family, Euphorbia is having more than 1600 species. The Euphorbiaceae family includes the annual weed Euphorbia hirta, sometimes referred to as the asthma plant. It's not just a weed, it also has medical properties. The Chinese Pharmacopoeia and African pharmacopoeia listed E. hirta for many drugs. Along with tropical and temperate regions of the world, Africa, Bangladesh, Australia and India are also home to these therapeutic herbs. The current review discusses its phytoconstituent profile, therapeutic profile and other significant biological characteristics. It includes a number of secondary active compounds, such as polyphenols, flavonoids, steroids, tannins and alkaloids, which act as anti-microbial, anti-fertility, anti-diabetic, anti-inflammatory, anti-cancer, anti-plasmodial, anti-tumor and in the management of many other disorders. Hematuria and gonorrhoea are also treated with E. hirta. In South Africa E. hirta is widely accepted as the prophylaxis of asthma. The herb is utilized as an enema remedy in the Gold Coast. Inflammatory bowel disease, psoriasis and diabetic-induced sores are just a few of the chronic inflammatory disorders that can be treated topically using the alcohol-based fruit and leaf extract of E. hirta. For the purpose of identifying and creating a monograph on E. hirta, this review may be used.